Networking of legal and organizational solutions in energy transition - Chrisidu-Budnik, Agnieszka (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The article focuses on the question of networking of legal and organizational solutions in the energy transition process, which accepts energy collectives. Energy collectives take on two fundamental forms in the Polish legal order: energy clusters and energy cooperatives. The article presents a description of these two basic legal and organizational mechanisms of energy transition and identifies the main indicators making it possible to compare them to each other. The paper uses the method of content analysis of legal regulations (EU and national) and specialised literature on the subject.
Keywords: energy transition; energy collectives; energy clusters; energy cooperatives